TANGGUNG JAWAB ORGAN PERSEROAN TERBATAS (PT) DALAM KEPAILITAN - -, Puspaningrum (Universitas Slamet Riyadi, 2011)
AbstractBankruptcy is a situation where the debtor is unable to make payments against the debts of the creditors. State can not afford the usual due to financial difficulties (financial distress) of the debitor who has suffered a setback. The main purpose of bankruptcy proceedings against the Limited Liability Company is to acceleratethe process of liquidation in the context of the distribution of company assets to pay debts that the company has experienced financial difficulties that caused the insolvency.Company Limited as a corporation having characteristics such as private law, including the separation of assets between the management company with Limited Liability, if a limited company into bankruptcy so that the company broke up how the management responsibilities of a Limited Liability Company? whether the management company can still be held liable or not Keywords: Company Limited, Bankruptcy.